The Possible Roles of Biological Bone Constructed with Peripheral Blood Derived EPCs and BMSCs in Osteogenesis and Angiogenesis. (18th April 2016) - Wu, Li; Zhao, Xian; He, Bo; Jiang, Jie; Xie, Xiao-Jie; Liu, Liu
Abstract : This study aimed to determine the possible potential of partially deproteinized biologic bone (PDPBB) seeded with bone marrow stromal cells (BMSCs) and endothelial progenitor cells (EPCs) in osteogenesis and angiogenesis. BMSCs and EPCs were isolated, identified, and cocultured in vitro, followed by seeding on the PDPBB. Expression of osteogenesis and vascularization markers was quantified by immunofluorescence (IF) staining, immunohistochemistry (IHC), and quantitive real-time polymerase chain reaction (qRT-PCR). Scanning electron microscope (SEM) was also employed to further evaluate the morphologic alterations of cocultured cells in the biologic bone. Results demonstrated that the coculture system combined with BMSCs and EPCs had significant advantages of (i) upregulating the mRNA expression of VEGF, Osteonectin, Osteopontin, and Collagen Type I and (ii) increasing ALP and OC staining compared to the BMSCs or EPCs only group. Moreover, IHC staining for CD105, CD34, and ZO-1 increased significantly in the implanted PDPBB seeded with coculture system, compared to that of BMSCs or EPCs only, respectively. Summarily, the present data provided evidence that PDPBB seeded with cocultured system possessed favorable cytocompatibility, provided suitable circumstances for different cell growth, and had the potential to provide reconstruction for cases with bone defection by promoting osteogenesis and angiogenesis.